2020
DOI: 10.3390/ijerph17217941
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Early-Onset Alzheimer’s Dementia and Frontotemporal Dementia: A Case-Control Study in Northern Italy

Abstract: Background: Early-onset dementia (EOD) is defined as dementia with symptom onset before 65 years. The role of environmental risk factors in the etiology of EOD is still undefined. We aimed at assessing the role of environmental risk factors in EOD etiology, taking into account its different clinical types. Methods: Using a case-control study, we recruited all EOD cases referred to Modena hospitals from 2016 to 2019, while the referent population was drawn from cases’ caregivers. We investigated residential his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 71 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…Following approval by the Modena Ethics Committee (n. 186/2016), we performed a case-control study on environmental and lifestyle risk factors for EOD in the province of Modena, Northern Italy. We recruited EOD cases from newly-diagnosed patients referred to the Cognitive Neurology Network of Modena province, including the Modena Policlinico-University Hospital Memory Center (Modena, Italy) and the Carpi Hospital Neurology Department (Carpi, Italy), in the period October 2016-2019 [7,24]. Cases are referred to this Network by either Neurology Units, primary care services, or general practitioners through specific pathways activated by the Modena Local Health Authority to identify and care for subjects with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…Following approval by the Modena Ethics Committee (n. 186/2016), we performed a case-control study on environmental and lifestyle risk factors for EOD in the province of Modena, Northern Italy. We recruited EOD cases from newly-diagnosed patients referred to the Cognitive Neurology Network of Modena province, including the Modena Policlinico-University Hospital Memory Center (Modena, Italy) and the Carpi Hospital Neurology Department (Carpi, Italy), in the period October 2016-2019 [7,24]. Cases are referred to this Network by either Neurology Units, primary care services, or general practitioners through specific pathways activated by the Modena Local Health Authority to identify and care for subjects with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…The supranutritional intake of selenium has been linked with increased risk of developing type 2 diabetes, advanced prostate cancer, hypertension, dyslipidemia, and neurodegenerative diseases (amyotrophic lateral sclerosis (ALS), early onset dementia, and Parkinson Disease) (Adani et al 2020a , b ; Bastola et al 2020 ; Loomba et al 2020 ; Vinceti et al 2018 , 2019a , b ; Wu et al 2018 ; Yarmolinsky et al 2018 ). In accordance with epidemiological studies, the intake of supranutritional levels of selenium, which were associated with an overexpression of two selenoenzymes [glutathione peroxidase 1 (GPx1) and methionine sulfoxide reductase (MsrB1)] has been shown to cause hyperinsulinemia and insulin resistance in mice (Labunskyy et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…After selection based on the pertinence and relevance to the topic of the review, 11,191 records were excluded, leaving 47 articles meeting the selection criteria. The full texts of the selected articles were assessed for inclusion, and 30 further articles were excluded as 3 were case reports [17,19,45], 1 review [46], 1 reported participation in sports as a leisure activity [47] 2 reported data only on an overall measure of physical activity [48,49] 2 included only athletes who had ≥ 1 head/brain injury [50,51] 8 did not report any measure of risk of NDs and/or NCDs [20,[52][53][54][55][56][57][58] and 13 were already included in the 2016 review [59][60][61][62][63][64][65][66][67][68][69][70][71].…”
Section: Resultsmentioning
confidence: 99%